Respon Pertumbuhan Seedling Anggrek Dendrobium Gradita 31 Pada Beberapa Kombinasi Media Ms dan Ekstrak Taoge - Dwi Dhita Apriyani; Yeni Yeni; Wika Anrya Darma; Lisa Erfa (Journal of Horticulture Production Technology, 2026)
Problems in orchid development are still quite limited due to the lack of availability of uniform seeds and the slow growth process of orchids, resulting in limited availability of orchid plant seeds. Subculture is the transfer of plants by in vitro culture from old media to new media with a specific purpose. One type of organic PGR used is bean sprout extract which contains auxin and cytokinin for the growth of plant seedlings. The objectives of this study are, (1) To obtain the best concentration of MS media at the growth stage of Dendrobium "Gradita" orchids, (2) To obtain the best concentration of bean sprout extract at the growth stage of Dendrobium "Gradita 31" orchids, (3) To determine the interaction between MS media and bean sprout extract at the growth stage of Dendrobium "Gradita 31" orchids, and (4) To obtain the best combination between MS media and bean sprout extract at the growth stage of Dendrobium "Gradita 31" orchids. The experiment will be conducted using a factorial Randomized Block Design (RAK). The first factor is the concentration of MS media, namely MS media ½ MS and full MS. The second factor is the concentration of bean sprout extract, namely 0 g.l-1, 100 g.l-1, 200 g.l-1, and 300 g.l-1. The research data were processed using analysis of variance, to see the differences between treatments, then continued with the Least Significant Difference (LSD) test at a level of 5%. The conclusions from the results of this study are (1) The best concentration of MS media use is at the level of concentration of bean sprout extract addition used in increasing seedling height, number of leaves, number of roots, root length, and seedling weight in the use of MS media. (2) The best concentration of bean sprout extract use is at the level of MS media use used in increasing seedling height, number of leaves, number of roots, root length, and seedling weight in the concentration of bean sprout extract 0 g.l-1 and 100 g.l-1. (3) There is an interaction between the combination of MS media and bean sprout extract on the increase in seedling height and seedling weight, and (4) There is the best combination of bean sprout extract, namely in ½ MS media with the addition of 0 g.1-1 bean sprout extract which results in an increase in seedling height, number of leaves, leaf length, and plant weight.